THE EFFECTIVIVITY OF MATHEMATICS COOPERATIVE LEARNING MODELS THINK PAIR SHARE (TPS) AND STUDENT TEAMS-ACHIEVEMENT DIVISIONS (STAD) COMBINED WITH SCIENTIFIC APPROACH IN TERM OF MATHEMATICAL COMMUNICATION SKILL OF STUDENTS GRADE 8 TH SMP N 1 SLEMAN - Ghosa Kurnia Fistika; Sugiyono Sugiyono (Jurnal Pedagogi Matematika, 2016)
AbstractThe  aim  of  this  study  was  to  determine:  (1)  the  effectiveness  of  cooperative  learning  model  Think  Pair Share  (TPS)  with  Scientific  approach  in  terms  of  mathematical  communication  skills  of  learners;  (2)  the effectiveness of cooperative learning model Student Teams-Achievement Divisions (STAD) with Scientific approach in  terms  of  mathematical  communication  skills  of  learners;  and  (3)  which  is  more  effective  among  cooperative learning  model  Think  Pair  Share  (TPS)  with  Scientific  approach  and  cooperative  learning  Student  Teams Achievement Divisions (STAD) with Scientific approach to mathematical communication skills of learners. This is a  quasi-experimental  study,  using  two  experimental  groups.  Instruments  to  measure  the  ability  of  mathematical communications in the form of shaped test item description. Based on hypothesis testing using a significance level of 5% can be concluded that: (1) cooperative learning model  type  TPS  with  scientific approach  was  effective  in terms of communication skills of mathematics, (2) cooperative learning model type STAD scientific approach  was effective  in terms of communication skills mathematical  ,  (3)  cooperative learning model  type  TPS with scientific approach  more effective than the cooperative learning model type STAD cooperative with the scientific approach in terms of mathematical communication skills.Keywords :  effectivity, cooperative learning model type Think Pair Share (TPS), cooperative learning model type  Student  Teams-Achievement  Division  (STAD),  scientific  approach,  mathematical communication skill.